High power, 100 W-class, thulium-doped all-fiber lasers - Michalska, Maria; Grześ, Paweł; Swiderski, Jacek (Photonics Letters of Poland, 2019)
In this work, sub-kilowatt, compact thulium-doped fiber laser systems, operating at a wavelength of 1940 nm, have been presented. The continuous-wave laser power generated out of a single oscillator was 90 W with a slope efficiency of 56.7%. Applying a master oscillator – power amplifier configuration, an output power of 120.5 W with a slope efficiency of 58.2% was demonstrated. These are the first results of the works aimed at developing kW-class “eye-safe” laser systems in Poland. Full Text: PDF References Z. Liu, et al., "Implementing termination analysis on quantum programming", Sci. China Inf. Sci. 62, 41301 (2019) CrossRef S. D. Jackson, A. Sabella, D.G Lancaster, "Application and Development of High-Power and Highly Efficient Silica-Based Fiber Lasers Operating at 2 μm", IEEE J. Sel. Top. Quantum Electron. 13, 567, (2007). CrossRef E. Russell, N. Kavanagh, K. Shortiss, and F. C. G. Gunning, "Development of thulium-doped fibre amplifiers for the 2μm waveband", Proc. SPIE 10683, 106832Q (2018) CrossRef P. Peterka, B. Faure, W. Blanc, M. Karásek, and B. Dussardier, "Theoretical modelling of S-band thulium-doped silica fibre amplifiers", Opt. Quantum Electron. 36, 201 (2004) CrossRef M. Eichhorn, "Pulsed 2 μm fiber lasers for direct and pumping applications in defence and security", Proc. SPIE 7836, 78360B (2010). CrossRef O. Traxer and E. X. Keller, "Thulium fiber laser: the new player for kidney stone treatment? A comparison with Holmium:YAG laser", World J. Urol. 2019 Feb 6. doi: 10.1007/s00345-019-02654-5 CrossRef S. Das, "Optical parametric oscillator: status of tunable radiation in mid-IR to IR spectral range based on ZnGeP2 crystal pumped by solid state lasers", Opt. Quant. Electron. 51, 70 (2019) CrossRef M. Michalska, P. Hlubina, and J. Swiderski, "Mid-infrared Supercontinuum Generation to ∼4.7 μm in a ZBLAN Fiber Pumped by an Optical Parametric Generator", IEEE Photon. J 9, 3200207 (2017) CrossRef https://www.ipgphotonics.com DirectLink M.D. Burns, P. C. Shardlow, P. Barua, T. L. Jefferson-Brain, J. K. Sahu, and W. A.Clarkson, "47 W continuous-wave 1726 nm thulium fiber laser core-pumped by an erbium fiber laser", Opt. Lett. 44, 5230 (2019) CrossRef S.D. Jackson, "Cross relaxation and energy transfer upconversion processes relevant to the functioning of 2 μm Tm3+-doped silica fibre lasers", Opt. Commun. 230, 197 (2004). CrossRef X. Wang, P. Zhou, X. Wang, H. Xiao, and L. Si, "102 W monolithic single frequency Tm-doped fiber MOPA", Opt. Express 21, 32386 (2013) CrossRef K. Yin, R. Zhu, B. Zhang, G. Liu, P. Zhou, and J. Hou, "300 W-level, wavelength-widely-tunable, all-fiber integrated thulium-doped fiber laser", Opt. Express 24, 11085 (2016) CrossRef G. D. Goodno, L. D. Book, and J. E. Rothenberg, "600-W, single-mode, single-frequency thulium fibre laser amplifier", Proc. SPIE 7195, 71950Y (2009). CrossRef T. Ehrenreich, R. Leveille, I. Majid, K. Tankala, G. Rines, and P. Moulton, "1-kW, all-glass Tm: fiber laser", Proc. SPIE 7580, 1 (2010) DirectLink M. Michalska et al., "Highly stable, efficient Tm-doped fiber laser—a potential scalpel for low invasive surgery", Laser Phys. Lett. 13, 115101 (2016). CrossRef